AN EXPLORATION STUDENT'S ERRORS IN SOLVING TRIGONOMETRIC RATIO PROBLEMS WITH ITS SCAFFOLDING - Nurdiyah Kurniati; Suhendra Suhendra; Nanang Priatna; Sufyani Prabawanto (Universitas Muhammadiyah Metro, 2022)
Trigonometry is an essential topic in learning mathematics, but in fact there are still identified student errors in solving trigonometry problems. Based on these problems, this study aims to describe students' errors in solving trigonometric problems, especially on the topic of trigonometric ratios and its scaffolding. This study uses a qualitative method with a case study approach. Collecting data through observation, tests and interviews. The subjects of this study were 35 students of class X in one of the senior high schools in Kutai Kartanegara Regency, East Kalimantan. The results of this study are that there are seven types of errors made by students in solving trigonometric ratio problems, namely: (1) error in understanding the concepts; (2) error in setting operation; (3) error in performing calculation; (4) error in applying the principle; (5) error in writing algorithm; (6) random response; and (7) error in drawing. Based on the results of these studies, it can be concluded that the forms of scaffolding that can be given are:explaining, reviewing, restructuring,and developing conceptual thinking.   Trigonometri merupakan materi yang esensial dalam pembelajaran matematika, namun pada faktanya masih terdapat kesalahan-kesalahan siswa yang teridentifikasi dalam menyelesaikan masalah trigonometri. Berdasarkan permasalahan tersebut, penelitian ini bertujuan untuk mendeskripsikan kesalahan-kesalahan siswa dalam menyelesaikan masalah trigonometri khususnya pada topik rasio trigonometri beserta scaffoldingnya. Penelitian ini menggunakan metode kualitatif dengan pendekatan studi kasus. Pengumpulan data melalui observasi, tes dan wawancara. Subjek penelitian ini adalah 35 siswa kelas X di salah satu SMAN di Kabupaten Kutai Kartanegara, Kalimantan Timur. Hasil penelitian ini yakni terdapat tujuh jenis kesalahan yang dilakukan siswa dalam menyelesaikan masalah rasio trigonometri, yaitu: (1) kesalahan dalam memahami konsep; (2) kesalahan dalam menetapkan operasi; (3) kesalahan dalam melakukan perhitungan; (4) kesalahan dalam menerapkan prinsip; (5) kesalahan dalam menuliskan algoritma; (6) jawaban sembarang; dan (7) kesalahan dalam menggambar. Berdasarkan hasil penelitian tersebut, dapat disimpulkan bahwa bentuk scaffolding yang dapat diberikan yaitu explaining, reviewing, restructuring, dan developing conceptual thinking.